Structure design of variable camber wing trailing edge based on multi-block rotating mechanism - SHI Xintong; YANG Yu; GE Wenjie; WANG Zhigang; SUN Xiasheng (Xibei Gongye Daxue Xuebao, 2023)
The variable camber trailing edge enables the aircraft to maintain the best aerodynamic performance throughout the flight envelope, so as to achieve the ultimate goal of reducing aircraft fuel consumption and air pollutant emissions. It is one of the important characteristics and development direction of the new generation civil aircraft. In order to solve the contradiction between the high load-bearing and the large deformation of the variable camber trailing edge of large aircraft, a structure scheme for variable camber trailing edge based on multi-block rotation was proposed. A parametric optimization method was established for smooth and continuous deformation of multi-block rotating mechanism. The multi-block rotating structure and driving system of variable camber trailing edge were designed, and the deformation function of the variable camber trailing edge demonstrator was preliminarily verified by ground test. The result shows that variable camber wing trailing edge designed by using the present optimization method of multi-block rotating mechanism can realize smooth and continuous morphing. The actual deformation range of the demonstration is 3.9 degrees up to 12.5 degrees down, and the error with the design target is 16.7%. It provides a design reference for solving the engineering application problem of variable camber structure for large aircraft.